Sample of eggs, feed, rice grains and DOD taken from center for traditional hatcheries of Alabio ducks in Mamar Village District of Hulu Sungai Utara South Kalirnantan were examined for Aspergillus contamination. The result showed that @40% of hatched eggs, 25-50% of feed, 0% of rice grairand 032.86% of DOD was contamined The species of Aspergillus found in those materials were Aspergillus flavus (18 isolates), Aspergillus fumigatus (12 isolates), Aspergillus niger (9 isolates) and AspergiUus - Bambang Ngaji Utomo (Media Veteriner, 1999)
Sample of eggs, feed, rice grains and DOD taken from center for traditional hatcheries of Alabio ducks in Mamar Village District of Hulu Sungai Utara South Kalirnantan were examined for Aspergillus contamination. The result showed that @40% of hatched eggs, 25-50% of feed, 0% of rice grairand 032.86% of DOD was contamined The species of Aspergillus found in those materials were Aspergillus flavus (18 isolates), Aspergillus fumigatus (12 isolates), Aspergillus niger (9 isolates) and AspergiUus sp. (9 isolates). Aspergillus content in feed sample examined was in the range between 2.0 X 103 - 2.3 X 103 colonies/gram.